Literature Review: Hospital Service Quality During The COVID-19 Pandemic - Salvany Zahra; Inge Dhamanti (Media Kesehatan Masyarakat, 2022)
Service quality is an important component in hospital management during the COVID-19 pandemic. During this pandemic, the lack of health workers and resources needed by patients may affect the quality of health services in hospitals. This review aims to provide an overview of the hospital quality services during the COVID-19 pandemic. The method used was literature review. Articles were searched through Google Scholar, Science direct and Pubmed with the keywords "health service quality" OR "quality of health services" AND “hospital” AND “COVID-19”. The total articles identified were 786, but only six articles matched the inclusion criteria. The results showed that there was a variation in the increase and decrease of hospital service quality during the pandemic. Therefore, health service should be provided optimally to maintain the quality of health services provided during the pandemic.